Gerakan Dakwah Salafi di Indonesia pada Era Reformasi - Hidayat, Dady (UI Scholars Hub, 2012)
This article examines the genesis and the expansion of salafi movements during reformation era. Using a social movement’s perspective with three main factors on social movements; political opportunity structure, framing process, and resources mobilization theory, this research aims to reveal the factor of salafi movement’s growing. The research is use a qualitative approach with a field research method, where the researchers directly observes to the people being studied and try to examine any subjective experiences in the sociological view. The results of this study reveal that the reformation era, gives some opportunity to salafi movements to be rapidly expanded. Their expanding is also supported by every social network they made, to gain resources and help the movements to do expanding of their activity.